2019
DOI: 10.3174/ajnr.a6097
|View full text |Cite
|
Sign up to set email alerts
|

Subject-Specific Studies of CSF Bulk Flow Patterns in the Spinal Canal: Implications for the Dispersion of Solute Particles in Intrathecal Drug Delivery

Abstract: BACKGROUND AND PURPOSE: Recent flow dynamics studies have shown that the eccentricity of the spinal cord affects the magnitude and characteristics of the slow bulk motion of CSF in the spinal subarachnoid space, which is an important variable in solute transport along the spinal canal. The goal of this study was to investigate how anatomic differences among subjects affect this bulk flow. MATERIALS AND METHODS: T2-weighted spinal images were obtained in 4 subjects and repeated in 1 subject after repositioning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 29 publications
2
35
1
Order By: Relevance
“…Several pathologic states are known to disrupt CSF flow dynamics, including the presence of bulk leptomeningeal deposits, postsurgical adhesions, and Chiari malformations (4). Recently, MRI studies have shown that anatomic differences, including lordosis and kyphosis, among healthy subjects affect CSF bulk flow; spinal cord eccentricity in the healthy human spine results in subject-specific patterns of recirculation of bulk CSF flow in certain regions (5).…”
Section: Discussionmentioning
confidence: 99%
“…Several pathologic states are known to disrupt CSF flow dynamics, including the presence of bulk leptomeningeal deposits, postsurgical adhesions, and Chiari malformations (4). Recently, MRI studies have shown that anatomic differences, including lordosis and kyphosis, among healthy subjects affect CSF bulk flow; spinal cord eccentricity in the healthy human spine results in subject-specific patterns of recirculation of bulk CSF flow in certain regions (5).…”
Section: Discussionmentioning
confidence: 99%
“…For a given subject, the necessary anatomical data can be determined from high-resolution MRI images, as explained for instance in Coenen et al. (2019). The computations reported below correspond to two subjects: a healthy 27-year-old female with cm, mm and (subject 1); and a healthy 39-year-old male with cm, mm and (subject 2), both with cardiac period s. The functions and shown in figure 1( b ) are obtained by the boundaries of the binary image stack resulting from segmentation of the high resolution MRI images.…”
Section: Illustrative Sample Applicationsmentioning
confidence: 99%
“…The results are compared in figures 2 and 3 with flow rate measurements acquired at 12 vertebral levels using PC-MRI with retrospective cardiac gating in in vivo experiments involving the two subjects (see Coenen et al. (2019) for details of the data-acquisition process). To establish a quantitatively consistent comparison, the results are presented in normalized form.…”
Section: Illustrative Sample Applicationsmentioning
confidence: 99%
See 2 more Smart Citations